Pengaruh Kebijakan Dividen, Kebijakan Hutang, Keputusan Investasi, Dan Profitabilitas Terhadap Nilai Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Nur Malasari; Abdul Rahman Mus; Amir Mahmud (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Abstract This study aims to determine the influence of dividend policy, debt policy, investment decisions, and profitability on firm value in the food and beverage sub-sector listed on the Indonesia Stock Exchange. Quantitative research was used. The population in this study consisted of 87 companies, with a sample of 17 food and beverage companies. The sampling technique employed was purposive sampling. SPSS was used for testing. Data analysis utilized multiple linear regression tests, coefficient of determination tests, simultaneous tests, and hypothesis tests. The results of this study indicate that dividend policy, measured by the Dividend Payout Ratio (DPR), has no significant effect; debt policy, measured by the Debt to Asset Ratio (DAR), has no significant effect; investment decisions, measured by the Price Earnings Ratio (PER), have no significant effect; and profitability, measured by the Net Profit Margin (NPM), has a significant effect on firm value, measured by the Price to Book Value (PBV), in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Dividend policy, measured by Dividend Yield, has no significant effect; debt policy, measured by the Total Interest Expense Ratio (TIER), has a significant effect; investment decisions, measured by the Return on Investment (ROI), have a significant effect; and profitability, measured by the Return on Assets (ROA), has a significant effect on firm value, measured by Tobin’s Q, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Dividend policy, measured by Dividend Per Share (DPS), has no significant effect; debt policy, measured by the Debt to Equity Ratio (DER), has no significant effect; investment decisions, measured by the Accounting Rate of Return (ARR), have a significant effect; and profitability, measured by the Return on Equity (ROE), has a significant effect on firm value, measured by Earnings Per Share (EPS), in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. This research contributes academically by strengthening the literature related to Dividend Policy, Debt Policy, Investment Decisions, Profitability, and Firm Value. At the same time, it provides practical implications for investors and companies in enhancing firm value. Keywords: Dividend Policy, Debt Policy, Investment Decisions, Profitability, Firm Value, Food and Beverage Companies.